PENGARUH PELATIHAN, MOTIVASI KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI KLINIK PRATAMA X - Salsabila Desindria; Recky Recky; Andhika Mochamad Siddiq; Kartika Nuradina (Jurnal Daya Saing, 2026)
The goal of this study is to “investigate the impact of training, work motivation, and compensation on employee performance at Klinik Pratama X”. This study uses a “quantitative method with an associative approach”. The sample group consists of 59 employees at Klinik Pratama X, and the full population was chosen as the sample using a saturation sampling method. Data were gathered by a “questionnaire and analyzed using SPSS Version 25 with multiple linear regression”. Before hypothesis testing, the data were checked for validity, reliability, and classical assumptions. The study's findings reveal that “training had no positive or significant influence on employee performance, with a significance level of 0.734”. Conversely, “job motivation and compensation have positive and substantial effects on employee performance, with p-values of 0.018 and 0.000, respectively”. At the same time, “training, work motivation, and salary all have a substantial effect on employee performance, with a p-value of 0.000, The coefficient of determination (R²) of 0.471 shows that these three variables account for 47.1% of the variation in employee performance, with the remaining 52.9% impacted by other factors”.